2019
DOI: 10.3390/app9040738
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Hand-Crafted Image Descriptors vs. Off-the-Shelf CNN-Based Features for Colour Texture Classification under Ideal and Realistic Conditions

Abstract: Convolutional Neural Networks (CNN) have brought spectacular improvements in several fields of machine vision including object, scene and face recognition. Nonetheless, the impact of this new paradigm on the classification of fine-grained images—such as colour textures—is still controversial. In this work, we evaluate the effectiveness of traditional, hand-crafted descriptors against off-the-shelf CNN-based features for the classification of different types of colour textures under a range of imaging condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 68 publications
2
50
0
Order By: Relevance
“…Since this set of rice seed images contain an object and are totally different, it does not outperform CNNbased methods. Similarly, we can see in the conclusion [44] that hand-crafted descriptors outperformed CNN-based features for colour texture classification. In the case of rice seed images, we found the opposite was true based on our experimental results.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Since this set of rice seed images contain an object and are totally different, it does not outperform CNNbased methods. Similarly, we can see in the conclusion [44] that hand-crafted descriptors outperformed CNN-based features for colour texture classification. In the case of rice seed images, we found the opposite was true based on our experimental results.…”
Section: Resultssupporting
confidence: 64%
“…In [42], [43], the authors propose to feed CNN by the new encoded image via Neighbor-Center Difference Image (NCDI) for texture classification. Bello-Cerezo et al [44] present a deep comparative evaluation of hand-crafted and CNN-based features for colour texture classification. The experimental results confirmed that hand-crafted descriptors give better performance than CNN-based features when there was little intra-class variability.…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural networks (CNNs) lie at the core of the best current architecture processing methods for both image and video data, primarily due to the advantages of CNNs in processing 2D input data (Cecotti and Graser, 2011). CNN has good performance in the field of biological image classification, and the features learned from CNN are often better than handcrafted features (Bello-Cerezo et al, 2019). The studies of Nanni et al (2019a;2019b) show that ensemble system of handcrafted and learned features can boost the performance of CNN in bioimage classification.…”
Section: Introductionmentioning
confidence: 99%
“…Before proceeding to definitions it is worth noting that, notwithstanding the trend towards the use of convolutional neural networks as feature extractors [14], rank features are still competitive in texture applications [15]. In the following section we recall the axioms for an order relation.…”
Section: Rank Featuresmentioning
confidence: 99%